CO2 electro-reduction on Cu3P: Role of Cu(I) oxidation state and surface facet structure in C1-formate production and H2 selectivity. (20th September 2021) - Laursen, Anders B.; Calvinho, Karin U.D.; Goetjen, Timothy A.; Yap, Kyra M.K.; Hwang, Shinjae; Yang, Hongbin; Garfunkel, Eric; Dismukes, G. Charles
Abstract: We report the catalytic activity and mechanism of copper(I) phosphide, Cu3 P, with predominant [00Ι] facet exposure for the electrochemical reduction of CO2 (CO2 RR) to formic acid. Crystalline nanosheets of this compound that show a preferential [00Ι] facet orientation exhibit undiminished CO2 RR activity after 16 hours with full retention of crystal structure and surface chemical speciation and no detectable corrosion. In contrast to the range of products formed on Cu metal, CuO, and Cu2 O, the CO2 RR on Cu3 P [00Ι] produces mainly hydrogen and formate as the sole carbon product in KHCO3 electrolyte. Analysis of the Cu3 P [00Ι] facet by HAADF-STEM was used to determine the surface lattice structure, while both XPS and Auger spectroscopies were used to determine the surface chemical speciation from the kinetic energies of ionized electrons. The presented analysis identifies isolated trigonal CuP3 sites on the Cu3 P[00Ι]-Cu3 P3 terminated surface and the Cu(I) oxidation state as precursor to the active catalyst. The CO2 RR selectivity to formate and the higher turnover rate for H2 production on the [00Ι] facet allows a structure-activity analysis and chemical mechanism to be proposed. Formation of a surface hydride at isolated *H-CuP3 sites is proposed as the catalytic site in forming both H2 and formate, while the long Cu—Cu separation retards forming C-C coupling products. These results disprove previously published claims of Cu(I) oxidation state as a sufficient criterion to promote CO2 RR to C2+ products, show that stronger bonded hydrides, *H-CuP3 on Cu3 P, favor production of the C1 product formate over all other carbon products, and predict that stronger formate binding (bidentate) is needed for CO2 RR currents to compete with H2 production. Graphical abstract: Image, graphical abstract